2015
DOI: 10.1002/ejhf.400
|View full text |Cite
|
Sign up to set email alerts
|

Detection of muscle wasting in patients with chronic heart failure using C‐terminal agrin fragment: results from the Studies Investigating Co‐morbidities Aggravating Heart Failure (SICA‐HF)

Abstract: Aims Skeletal muscle wasting affects 20% of patients with chronic heart failure and has serious implications for their activities of daily living. Assessment of muscle wasting is technically challenging. C‐terminal agrin‐fragment (CAF), a breakdown product of the synaptically located protein agrin, has shown early promise as biomarker of muscle wasting. We sought to investigate the diagnostic properties of CAF in muscle wasting among patients with heart failure. Methods and results We assessed serum CAF levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 45 publications
3
70
0
Order By: Relevance
“…Both morphological alterations of NMJs (motor nerve terminals and nAChR clusters) and resulting of sciatic nerve stimulated-EPPs during the TR suggest that motor nerve denervation could be mainly involved in disability of NMJ transmission during early stage of TR, while fragmentation of nAChR clusters possibly is the key factor that causes inefficiency of NMJ transmission during late-stage of TR. Some previous studies have shown that fragmentation of an individual nAChR cluster might correlate with a decline in efficacy of the neuromuscular transmission in pathophysiological states (Maselli et al, 1995; Gonzalez-Freire et al, 2014; Steinbeck et al, 2015; Vescovo, 2015; Willadt et al, 2016). Our current study further demonstrates that dysfunction of NMJ transmission is mediated by both motor nerve denervation and the fragmentation of nAChR clusters during TR.…”
Section: Discussionmentioning
confidence: 97%
“…Both morphological alterations of NMJs (motor nerve terminals and nAChR clusters) and resulting of sciatic nerve stimulated-EPPs during the TR suggest that motor nerve denervation could be mainly involved in disability of NMJ transmission during early stage of TR, while fragmentation of nAChR clusters possibly is the key factor that causes inefficiency of NMJ transmission during late-stage of TR. Some previous studies have shown that fragmentation of an individual nAChR cluster might correlate with a decline in efficacy of the neuromuscular transmission in pathophysiological states (Maselli et al, 1995; Gonzalez-Freire et al, 2014; Steinbeck et al, 2015; Vescovo, 2015; Willadt et al, 2016). Our current study further demonstrates that dysfunction of NMJ transmission is mediated by both motor nerve denervation and the fragmentation of nAChR clusters during TR.…”
Section: Discussionmentioning
confidence: 97%
“…8- 10 The Studies Investigating Co-morbidities Aggravating Heart Failure (SICA-HF) was a multi-national, pathophysiological observation study into HF and its comorbidities. 11, 12 August 2013. During that period we recruited 275 patients and 52 controls.…”
mentioning
confidence: 99%
“…The same problem applies to other mechanistic pathways that have been identified as principle pathologic mechanisms in the progression of HF. Metabolic failure in HF is recognized to account for impaired energy metabolism as well as for impaired structural metabolism leading to muscle wasting and eventually cardiac cachexia . Insulin resistance is a key characteristic feature in HF underlying metabolic failure .…”
mentioning
confidence: 99%